GLOBAL GEOPOLITICS AMIDST THE THREAT OF THE COVID-19 PANDEMIC - Kunkunrat Kunkunrat (INFOKUM, 2021)
Global Geopolitics amidst the Threat of the Covid-19 Pandemic has become the focus of this research to understand the impact of the pandemic on the dynamics of international relations. The research background includes shifts in global political, economic and security forces influenced by the spread of the virus. The aim of the research is to analyze countries' responses to the pandemic in a geopolitical context, as well as identify collaboration and conflict strategies that emerge amidst the crisis. The research method used is a descriptive qualitative approach. The research results show that the COVID-19 pandemic has brought about significant changes in global geopolitics. Some Asian countries showed impressive resilience in responding to the crisis, while countries with traditional global leadership faced challenges. The dynamics of government, both democratic and authoritarian, in responding to the pandemic are the focus of debate. International cooperation and the role of international organizations, especially WHO, are recognized as important in dealing with global health threats. At the regional level, Southeast Asia is faced with the need to increase unity and resilience in order to maintain relevance on the international stage .